Temperature mapping of operating nanoscale devices by scanning probe thermometry - Fabian Menges (Nature Portfolio, 2016)
Thermometry using scanning probe techniques allows for the thermal imaging and characterization of devices with nanoscale resolution, however can be hindered by contact-related artefacts. Here, the authors demonstrate a thermal scanning probe approach which eliminates contact-resistance effects.